1997
DOI: 10.1002/(sici)1097-0320(19970101)27:1<43::aid-cyto6>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis and confocal imaging of anticancer alkylaminoanthraquinones and their n‐oxides in intact human cells using 647‐nm krypton laser excitation

Abstract: Flow cytometry and laser-scanning confocal fluorescence microscopy have been used in the study of the pharmacodynamics, in single intact cells, of two novel alkylaminoanthraquinones (AQ4 and AQ6), structurally based upon the mid-red excitable but very weakly fluorescent anticancer agent mitoxantrone, together with their respective N-oxide derivatives (AQ4NO and AQ6NO). The drug design rationale was that N-oxide modifications generates prodrug forms suitable for selective bioreductive-activation in hypoxic tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 10 publications
2
20
0
Order By: Relevance
“…oxic or hypoxic) cell populations. However, with AQ4N the observed enhancement is maintained even when drug is administered up to 16 h before radiation in the SCCVII tumour model (Figure 4); the stability and DNA affinity of AQ4 is likely to explain this phenomenon (Smith et al, 1997a;1997b). Once produced, AQ4 will persist in the hypoxic cell fraction and kill any cell which attempts to re-enter the cell cycle following destruction of oxic cells by irradiation.…”
Section: Enhancement Of Radiation Therapy By Aq4nmentioning
confidence: 99%
See 1 more Smart Citation
“…oxic or hypoxic) cell populations. However, with AQ4N the observed enhancement is maintained even when drug is administered up to 16 h before radiation in the SCCVII tumour model (Figure 4); the stability and DNA affinity of AQ4 is likely to explain this phenomenon (Smith et al, 1997a;1997b). Once produced, AQ4 will persist in the hypoxic cell fraction and kill any cell which attempts to re-enter the cell cycle following destruction of oxic cells by irradiation.…”
Section: Enhancement Of Radiation Therapy By Aq4nmentioning
confidence: 99%
“…In contrast, we report here preclinical data on a new class of bioreductive agent exemplified by AQ4N (1,4-bis-{[2-(dimethylamino-N-oxide)ethyl]amino}5,8-dihydroxyanthracene-9, 10-dione). This agent is a prodrug designed to be excluded from cell nuclei (Patterson, 1993;Smith et al, 1997b) until metabolized in hypoxic cells to give AQ4, a stable, oxygeninsensitive metabolite (Smith et al, 1997a) (Figure 1). AQ4 is a DNA intercalator and potent inhibitor of DNA type II topoisomerase (Patterson, 1993;Patterson et al, 1994;Smith et al, 1997a).…”
mentioning
confidence: 99%
“…7 (188)) permits fluorescence microscopy and flow cytometry to determine uptake and nuclear distribution. Subcellular and nuclear distribution patterns reveal drug resistance (189), altered behavior of alkylamino-anthraquinones and the impact of N-oxide derivatization (160). The structurally related far-red fluorescent DNA dyes and the nuclear counterstains DRAQ5™ (128,(190)(191)(192), DRAQ7™ (89,132,(193)(194)(195), and the spectrally shifted CyTRAK Orange™ (196) have applications in nuclear cytometry (197).…”
Section: One Man's Probe Is Another Man's Poisonmentioning
confidence: 99%
“…These unidirectional HAPS (uHAPs) are reduced in hypoxia to the metabolically stable reduction products (AQ4 and OCT1001, respectively). Studies with AQ4N and OCT1002 show that hypoxia‐mediated reduction results in a product with high affinity for DNA and targeting of topoisomerase II,which can effect a long‐term inhibition of both DNA replication and G2/M cell transition …”
Section: Introductionmentioning
confidence: 99%
“…Studies with AQ4N and OCT1002 show that hypoxiamediated reduction results in a product with high affinity for DNA and targeting of topoisomerase II, 23,24 which can effect a long-term inhibition of both DNA replication and G2/M cell transition. 25,26 Previously we have shown that OCT1002 kills hypoxic prostate cancer cells in vitro and in vivo. 21 We provided the first evidence that OCT1002 has a hypoxia-dependent anti-tumor effect in androgensensitive LNCaP prostate tumor xenografts and the effect can be markedly enhanced when combined with daily bicalutamide administration, a drug which targets the androgen receptor (AR).…”
mentioning
confidence: 99%